(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Cancer is reason death number two in the world. Bitter melon has component bioactive that shows potency activity anti-cancer. Extract bitter melon fruit is known as anti- cancer in human breast cancer cells, MCF-7 and MDA-MB-231, Objectives: Objective study in vitro, knowing caspase 3 expression and amount cells undergoing apoptosis in the given T47 D cell culture extract bitter melon. Methodology Study experimental laboratory with post-test only randomized control group design.T47 D cell culture samples group control and group treatment each as many as 3 wel with density 5x10 4 cells /100 μl, each well filled with T47 D cell culture density cells 5x10 4 cells /100 μl, given extract ethanol bitter melon fruit dose ½ IC 50. IC50 and 2 IC50, incubation for 24 hours. After 24 hours, the Coverslip is removed and carried out painting immuno cytochemistry for see expression caspase -3 and Fluocytometry for see the number of cells undergoing apoptosis Data on caspase 3 expression were tested with One-way anova test and Post hoc test. Fluocytometry data, served in a way descriptive. Result The IC50 dose resulted in a value of 269.4 μg/mL. The average expression of caspase-3 in T47D cell cultures was 15.23+2.05 in the control group, 21.17+1.44 in the half IC50 dose group, and the highest in the IC50 dose group was 23.28+2.25. The lowest expression of caspase-3 in T47D cells was found in the group with a dosage of 2 IC50, which was 7.58+0.68. The amount of apoptotic cells with Fluocytometry was increased expression . The highest amount of apoptotic cells was found in the 2 IC50 dose group, whereas it was the lowest in the 1/2 IC50 dose group. Conclusion Ethanol extrac of bitter melon fruit has anti cancer activity. BJMS, Vol. 25 No. 02 April’26 Page: 558-565